Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Michaud, D; Izard, J; Rubin, Z; Johansson, I; Weiderpass, E; Tjønneland, A; Olsen, A; Overvad, K; Boutron-Ruault, M; Clavel-Chapelon, F; Dossus, L; Kaaks, R; et al. (2013)
Background: Increasing evidence suggests that oral microbiota play a pivotal role in chronic diseases, in addition to the well-established role in periodontal disease. Moreover, recent studies suggest that oral bacteria may also be involved in carcinogenesis; periodontal disease has been linked to several cancers. In this study, we examined whether lifestyle factors have an impact on antibody levels to oral bacteria. Methods: Data on demographic characteristics, lifestyle factors, and medical conditions were obtained at the time of blood sample collection. For the current analysis, we measured antibody levels to 25 oral bacteria in 395 cancer-free individuals using an immunoblot array. Combined total immunoglobin G (IgG) levels were obtained by summing concentrations for all oral bacteria measured. Results: IgG antibody levels were substantially lower among current and former smokers (1,697 and 1,677 ng/mL, respectively) than never smokers (1,960 ng/mL; p trend = 0.01), but did not vary by other factors, including body mass index, diabetes, physical activity, or by dietary factors, after adjusting for age, sex, education, country, and smoking status. The highest levels of total IgG were found among individuals with low education (2,419 ng/mL). Conclusions: Our findings on smoking are consistent with previous studies and support the notion that smokers have a compromised humoral immune response. Moreover, other major factors known to be associated with inflammatory markers, including obesity, were not associated with antibody levels to a large number of oral bacteria. © 2013 Springer Science+Business Media Dordrecht.